Assessment of the essential oil extracted from Citrus aurantifolia leaves using solvent-free microwave extraction technique - G.M. Masud Rana; Md. Jasim Uddin; Jaytirmoy Barmon; Bijoy Chandra Ghos; Tahmina Akter Chowdhury; Amit Kumar Dey; Bijoy Maitra; Ismat Moin Tamanna; AHM Mahbubur Rahman; Barun Kanti Saha; Mst. Sarmina Yeasmin (Food Chemistry Advances)
Citrus aurantifolia is a widely cultivated species with various culinary and medicinal applications. Essential oil (EO) extracted from Bangladeshi C. aurantifolia leaves was evaluated for its potential to act as a bioactive, antioxidant, and antibacterial agent. EO was obtained from C. aurantifolia leaves using solvent-free microwave extraction (SFME). Gas chromatography-mass spectrometry (GC–MS) profiling revealed multiple bioactive components in C. aurantifolia leaves EO, with neral (30.728 %), d-limonene (22.824 %), citral (19.430 %), lemonol (5.060 %), geraniol (3.447 %), geranial (3.079 %), and caryophyllene (3.959 %) being the major components. The IC50 value of the extracted EO was 8.05 ppm comparing with the value of 10.63 ppm for Butylated hydroxytoluene (BHT). Which revealed that C. aurantifolia leaves EO had better antioxidant properties than the standard BHT. The EO also exhibited antimicrobial action against gram-positive Listeria monocytogenes (ATCC 13,932) and gram-negative Escherichia coli, Pseudomonas aeruginosa and S. choleraesuis (ATCC 10,708). The zone of inhibition of EO varied from 6.52 to 18.1 mm. The potency of EO against S. choleraesuis, E. coli, L. monocytogenes, and P. aeruginosa was demonstrated by the reaction orders of 0.5588, 0.163, 0.2663, and 0.0871, respectively. These findings suggest possible applications of EO in both the pharmaceutical and food sectors, as an antioxidant and an antimicrobial.